Vers des frontières plus claires entre restauration et hyper-restauration - Hélène Verougstraete (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
After visiting the exhibition Fake or not Fake, held in the Bruges Groeningemuseum, November 2004-February 2005, art historians were essentially struck by the revelations about Van der Veken. But the purpose was to demonstrate to the public that works of art should be submitted to a critical examination, like any archival source. The eye is not sufficient. The help of technical instruments is necessary. Inorder to protect the works of art, one should consider the legal aspects of the restorer's activity.